Arbitraż od totalitarnych czasów PRL po czasy współczesne – uwagi porównawcze na tle zakresu przedmiotowego dopuszczalności arbitrażu - Fruk, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The fundamental determinant of the functioning of arbitration is the establishment of a viable alternative to the state judiciary. However, in some cases (due to their special nature) it is necessary for state courts to maintain a monopoly of adjudication. As a result, regulations relating to the substantive scope of arbitrability play a relevant role within the rules governing arbitration. The rules on arbitrability have undergone constant modifications — from the totalitarian times of the People’s Republic of Poland to the modern era. This is in undoubted connection with changes in the scope of the domestic social and economic system. The subject scope of permissibility of arbitration is constantly liberalizing. The changes being introduced are aimed at bringing the domestic regulation of arbitrability in line with international standards. The legislator is also revising the arbitration rules in the scope in question — thus eliminating relevant doubts regarding their interpretation, which is also showing significant importance for the practice of arbitration. Consequently, it seems that one can risk stating that, in the final effect, the analyzed legislative actions have a chance to make arbitration a viable alternative to proceedings before a common court.
Keywords: arbitraż; sądownictwo polubowne; zakres dopuszczalności arbitrażu; przedmiotowy zakres dopuszczalności arbitrażu; zdatność arbitrażowa; arbitraż a ustrój społeczno-gospodarczy